Pre-Columbian origins for North American anthrax. - Leo J Kenefic; Talima Pearson; Richard T Okinaka; James M Schupp; David M Wagner; Alex R Hoffmaster; Carla B Trim; Wai-Kwan Chung; Jodi A Beaudry; Lingxia Jiang; Pawel Gajer; Jeffrey T Foster; et al. (PLoS ONE)
Disease introduction into the New World during colonial expansion is well documented and had a major impact on indigenous populations; however, few diseases have been associated with early human migrations into North America. During the late Pleistocene epoch, Asia and North America were joined by the Beringian Steppe ecosystem which allowed animals and humans to freely cross what would become a water barrier in the Holocene. Anthrax has clearly been shown to be dispersed by human commerce and trade in animal products contaminated with Bacillus anthracis spores. Humans appear to have brought B. anthracis to this area from Asia and then moved it further south as an ice-free corridor opened in central Canada approximately 13,000 ybp. In this study, we have defined the evolutionary history of Western North American (WNA) anthrax using 2,850 single nucleotide polymorphisms (SNPs) and 285 geographically diverse B. anthracis isolates. Phylogeography of the major WNA B. anthracis clone reveals ancestral populations in northern Canada with progressively derived populations to the south; the most recent ancestor of this clonal lineage is in Eurasia. Our phylogeographic patterns are consistent with B. anthracis arriving with humans via the Bering Land Bridge. This northern-origin hypothesis is highly consistent with our phylogeographic patterns and rates of SNP accumulation observed in current day B. anthracis isolates. Continent-wide dispersal of WNA B. anthracis likely required movement by later European colonizers, but the continent's first inhabitants may have seeded the initial North American populations.